Commiphora omundomba (Burseraceae), a new species from Angola and Namibia - Swanepoel, Wessel; Weeks, Andrea; van Wyk, Abraham E. (Phytotaxa, 2022)
Commiphora omundomba, described here as a new species, is known only from the Kaokoveld Centre of Endemism, a biogeographical region in southwestern Angola and Northwestern Namibia. It has hitherto been confused with C. dinteri from west-central Namibia, but both morphological and molecular evidence support a distinction between the two species. Phylogenetic analysis of DNA sequence data indicates that C. omundomba shares most-recent common ancestry with C. buruxa, a species limited to the Gariep Centre of Endemism in southwestern Namibia. Diagnostic morphological characters for C. omundomba include the white, viscous exudate, smooth bark and glabrous, trifoliolate leaves. Photographs of the plant and a distribution map are provided. The new species is mainly confined to near the Atlantic coast of the northern Namib Desert, and is widespread and locally common between Santa Maria in Angola and Puros in Namibia.